Clinical Profile, Prognostic Factors, and Outcome Prediction in Hospitalized Patients With Bloodstream Infection: Results From a 10-Year Prospective Multicenter Study - Jin, Longyang; Zhao, Chunjiang; Li, Henan; Wang, Ruobing; Wang, Qi; Wang, Hui (Frontiers in Medicine, 2021)
Background Bloodstream infection (BSI) is one of the most common serious bacterial infections worldwide and also a major contributor to the in-hospital mortality. Determining the predictors of mortality is crucial for prevention and improving clinical prognosis in patients with nosocomial BSI. Methods A nationwide prospective cohort study was conducted from 2007 until 2016 in 16 teaching hospitals across China. Microbiological results, clinical information and patient outcome were collected to investigate the pathogenic spectrum and mortality rate in patients with BSI and identify outcome predictors using multivariate logistic regression, prediction model and Kaplan-Meier analysis. Results No significant change was observed in the causative pathogen distribution during the ten-year period and the overall in-hospital mortality was 12.83% (480/3741). An increased trend was found in mortality of patients in infection with P. aeruginosa or A. baumannii, while a decreased mortality rate was noted in S. aureus-related BSI. In multivariable-adjusted models, higher mortality rate was significantly associated with older age, cancer, sepsis diagnosis, ICU admission and prolonged hospital stay prior to BSI onset, which were also determined using machine learning-based predictive model achieved by random forest algorithm with a satisfactory performance in outcome prediction. Conclusions Our study described clinical and microbiological characteristics and mortality predictive factors in patients with BSI. These informative predictors would inform clinical practice to adopt effective therapeutic strategies to improve patient outcome.